Oligocene lacustrine tuff facies, Abu Treifeya, Cairo-Suez Road, Egypt. (February 2015) - Abdel-Motelib, Ali; Kabesh, Mona; El Manawi, Abdel Hamid; Said, Amir
Highlights: Oligocene lacustrine volcaniclastic deposits are recorded at Abu Treifeya area. These deposits are subdivided into: proximal and medial facies. New record of saponite associated with lacustrine zeolite deposits was identified. Saponite is attributed to a warm climate with alternating humid and dry conditions. Abstract: Field investigations in the Abu Treifeya area, Cairo-Suez District, revealed the presence of Oligocene lacustrine volcaniclastic deposits of lacustrine sequences associated with an Oligocene rift regime. The present study represents a new record of lacustrine zeolite deposits associated with saponite clay minerals contained within reworked clastic vitric tuffs. The different lithofacies associations of these clastic sequences are identified and described: volcaniclastic sedimentary facies represent episodic volcaniclastic reworking, redistribution and redeposition in a lacustrine environment and these deposits are subdivided into proximal and medial facies. Zeolite and smectite minerals are mainly found as authigenic crystals formed in vugs or crusts due to the reaction of volcanic glasses with saline–alkaline water or as alteration products of feldspars. The presence of abundant smectite (saponite) may be attributed to a warm climate, with alternating humid and dry conditions characterised by the existence of kaolinite. Reddish iron-rich paleosols record periods of non-deposition intercalated with the volcaniclastic tuff sequence.